2013
DOI: 10.1038/cddis.2013.290
|View full text |Cite
|
Sign up to set email alerts
|

BRCC2 inhibits breast cancer cell growth and metastasis in vitro and in vivo via downregulating AKT pathway

Abstract: In our previous study, we demonstrated that the BRCC2 (breast cancer cell 2) gene is a proapoptotic molecule that interacts with Bcl-XL. BRCC2 downregulation is associated with poor disease-free and overall survival in breast cancer. In this study, we aimed to investigate the role of BRCC2 in tumor suppression in breast cancer. In clinical breast cancer samples, we found that BRCC2 expression was significantly downregulated in cancer lesions compared with paired normal breast tissues. By silencing or overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Recent studies have revealed that miRNAs act as an important regulator of gene expression at the post-transcriptional level and regulates a wide range of physiological and developmental processes[ 16 19 ]. Over the past several years, it has become clear that deregulated of miRNAs contribute to the development of most human cancers such as gastric cancer, bladder cancer and breast cancer, which they act as either oncogenes or tumor suppressors[ 20 23 ]. In the present study, we investigated the role of miR-377 in human HCC development.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that miRNAs act as an important regulator of gene expression at the post-transcriptional level and regulates a wide range of physiological and developmental processes[ 16 19 ]. Over the past several years, it has become clear that deregulated of miRNAs contribute to the development of most human cancers such as gastric cancer, bladder cancer and breast cancer, which they act as either oncogenes or tumor suppressors[ 20 23 ]. In the present study, we investigated the role of miR-377 in human HCC development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has suggested that ILK regulates cell survival through the PI3K/Akt pathway (32), which has also been implicated in cancer cell (33,34) and CSC survival (35,36), cancer cell proliferation (37,38), and the CSC phenotype (39). We found that knockdown of ILK reduced the phosphorylation of Akt (Figure 4A; Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Among the miRNAs without previously reported association and whose biological functions have not been characterized in PCa are hsa-miR-1973, hsa-miR-575, hsa-miR-630 and hsa-miR-600. hsa-miR-575 and the hsa-miR-630 are proposed oncomiRNAs in other tumors such as gastric cancer, lung cancer, renal cell carcinoma, hepatocellular carcinoma, and breast cancer [34][35][36][37][38][39][40]. hsa-miR-630 has different gene targets such as BCL-2, MTDH, YAP-1, SNAI2 [37][38][39] involved in PCa oncogenesis [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…hsa-miR-575 has as a target BLID (BH3-like motif containing, BRCC2). BLID is a tumor-suppressor gene involved in DNA repair and gene integrity [40]. In breast cancer, BLID inhibited cancer cell growth and metastasis via downregulating AKT pathway [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation